The factors influencing the effective early career and rapid transition to a nursing specialty in differing contexts of practice: a modified Delphi consensus study - Diane Chamberlain; Desley Hegney; Clare Harvey; Bruce Knight; Anne Garrahy; Lily Pei-San Tsai (BMJ Open)
Objectives This study aimed to test and further develop the ‘Early Career and Rapid Transition to a Nursing Specialty’ (TRANSPEC) model to a nursing specialty developed from a systematic review. Semi-structured interviews of specialist clinically based nurses and a consensus Delphi study with an expert panel were used to expand and achieve consensus, agreement, reliability and stability of the model.Design A modified Delphi, two rounds (64 and 52 Likert items) of reiterative online questionnaires and one round as a nominal group technique, was informed by qualitative thematic analysis of semi-structured interviews.Setting and participants Interviews with 14 specialists clinical practicing registered nurses and a panel of 25 national experts participated in the Delphi study.Results The interview participants experienced 14 rapid transitions and three were early career transition. The overarching themes from the preliminary model were confirmed and further expanded. These were the self (personal and professional); the transition processes (final and informal); a sense of belonging; and the overarching context of practice over a time continuum. In the Delphi, the highest rating item was ‘Specialty work colleagues respect, include, support, and accept specialist nurse on completion of transition processes’. Pre-entry was highlighted as an important time point prior to transition. All items reaching consensus were included in the final model. Cronbach α increased from 0.725 to 0.875 for the final model.Conclusions The TRANSPEC model is a valid and reliable evidence-based tool for use in the career pathway and development of nursing specialists. Using the Benner model ‘Novice to Expert’ after the novice incomer phase is achieved, further lifelong learning development will transform the novice specialist over time continuum.